Hazard analysis of future surface displacements on active faults based on the recurrence interval of strong earthquakes - Zhou Qingyun; Liu Jingnan; Tian Peng; Luo Weidong; Bai Xianfu; Yang Yue; Zou Zhenyu (Open Geosciences)
Coseismic surface displacements pose a serious threat to the safety of linear infrastructures on active faults. A reasonable evaluation of surface displacements on active faults is important. Probabilistic fault displacement hazard analysis (PFDHA) is often used for surface displacement evaluation. However, PFDHA, developed based on the classical probabilistic method, requires an in-depth study of the activity parameters of all active faults in seismic–tectonic zones, greatly limiting its application in engineering design. The recurrence interval of strong earthquakes is a readily obtainable parameter of fault activity. In this study, we combine this key parameter with various seismic indicators to develop a comprehensive algorithm to assess potential future surface displacement hazards. In addition, the factors affecting the method are analyzed, and the surface displacements of several earthquakes with a magnitude of 7 or above are compared. The results indicate that the predicted future surface displacements using our method are greater than the true displacements of seismic events. For easy use, the exceedance probability–displacement (horizontal and vertical) curves of 27 strong earthquake recurrence intervals are given. This facilitates structural designers to quickly obtain future displacement values in structural design.